Answer:
![t_3 = -53\\\\\\t_7 = -17\\t_n= -80 +9n](https://img.qammunity.org/2023/formulas/mathematics/high-school/vvdiwl0tl53r0nhvv19qs4zq3x97kyx0nd.png)
Explanation:
Arithmetic sequence:
![\sf \boxed{t_n=a+(n-1)d}](https://img.qammunity.org/2023/formulas/mathematics/high-school/fvhysls6yczlzctpjbr0giholh6gvx7cs3.png)
Here a is the first term and d is the common difference.
⇒
------------(I)
⇒ a + 19d = 100 ---------(II)
Subtract equation (I) from (II)
(I1) a + 19d = 100
(II) a + 13d = 46
- - -
6d = 54
d = 54 ÷ 6
![\sf \boxed{d = 9}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8imceot03b3xm7vwfwqq6ow9ccd69wg10y.png)
Substitute d = 9 in equation(I) and find 'a',
a + 13*9= 46
a + 117 = 46
a = 46 - 117
a = -71
![\sf t_3 = -71 + 2*9](https://img.qammunity.org/2023/formulas/mathematics/high-school/cbo5ac3sehy03blukhmkkndqd9uwzomxhf.png)
= -71 + 18
= -53
![\sf t_7 = -71 + 6*9](https://img.qammunity.org/2023/formulas/mathematics/high-school/cdq4kmk4sufyb6daavcnoui2bzwyflvzv1.png)
= -71 + 54
= -17
![\sf t_n= -71 + (n-1)*9](https://img.qammunity.org/2023/formulas/mathematics/high-school/r86z7d6g7cxt435sddoe8hy4njqbysailn.png)
= -71 + 9*n - 1 *9
= -71 + 9n - 9
= -71 - 9 + 9n
= - 80 + 9n